Prisons: ignore them at our peril. Issue 5 (September 2019) - Kamarulzaman, Adeeba; Verster, Annette; Altice, Frederick L.
Abstract : Purpose of review: People with HIV and HCV are concentrated within criminal justice settings globally, primarily related to criminalization of drug use. This review examines updated prevention and treatment strategies for HIV and HCV within prison with a focus on people who inject drugs and the challenges associated with the provision of these services within prisons and other closed settings and transition to the community. Recent findings: The prevalence of HIV and HCV are several-fold higher in the criminal justice system than within the broader community particularly in regions with high prevalence of injecting drug use, such as Asia, Eastern Europe and North America and where drug use is criminalized. Strategies to optimize management for these infections include routine screening linked to treatment within these settings and medication-assisted treatments for opioid dependence and access to syringe services programs. We build upon the 2016 WHO Consolidated Guidelines through the lens of the key populations of prisoners. Linkage to treatment postrelease, has been universally dismal, but is improved when linked to medication-assisted therapies like methadone, buprenorphine and overdose management. In many prisons, particularly in low-income and middle-income settings, provision of even basic healthcare including mental healthcare and basic HIV prevention tools remain suboptimal. Summary: In order to address HIV and HCV prevention and treatment within criminal justice settings, substantial improvement in the delivery of basic healthcare is needed in many prisons worldwide together with effective screening, treatment and linkage of treatment and prevention services to medication-assisted therapies within prison and linkage to care after release.